Pengunaan metode modifikasi dalam meningkatkan kemampuan smash permainan bolavoli - Noprian, Ardi; Zulrafli; Kamarudin (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The success of teachers in the learning process in schools is largely determined by the method used. Applying the right method will give good results. This study aims to determine the increase in volleyball learning ability. The subjects of this study were 39 male students. This type of research is Classroom Action Research (PTK). This data collection uses the ability of students to make modification methods in volleyball smash learning using performance tests (psychomotor). The results of this study are an increase in the satisfactory learning achievement of volleyball using the modified method. In the assessment before the student completeness cycle was 12.8% (5 people), the student completeness in the first cycle assessment was also 12.8% (5 people), while the student completeness in the second cycle assessment was 43.6% (17 people). This proves that the modification method is able to improve the volleyball game smash skills of class XI students of SMK Kansai Pekanbaru. In future research recommendations, it is hoped that other researchers will use this modified method in learning physical education in schools to be more interesting and creative in modifying it and using a large number of samples.